Perancangan Buku Ajar Berbasis Saintifik Pada Mata Pelajaran Teknologi Perkantoran di SMK Ketintang Surabaya - Nurulloh Nurulloh; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this researh is to determine the results of the development of scientific-based textbooks at office technology subjects at SMK Ketintang Surabaya. The office technology teacher at Ketintang Vocational School in Surabaya stated that teaching materials in the form of textbooks did not exist before. This whole time, the teacher uses LKS and materials found from the internet for the learning activities. However, the LKS used is not in accordance with the syllabus in the revised edition of the 2013 curriculum which emphasizes on the scientific learning (5M). This definitely does not reflect the characteristics of learning that should be student-centered. The type of research used is Research and Development (R&D) with the 4D development model developed by Thiagarajan, namely defining, designing, developing, and disseminating. However, this research was only carried out until the design stage only due to the limitations in this study. The results of this research are analyzing the textbooks that will be developed which begin with the define stage which includes the preliminary analysis, analysis of students, task analysis, concept analysis, and specifications of learning objectives. Next step is the design phase which includes the preparation of the textbook, the selection of the textbook format, and the design of the textbook itself. Therefore, it is expected that the development of scientific-based textbooks in office technology subjects at SMK Ketintang Suarabaya can help the teachers to deliver the learning materials and can facilitate students in understanding those materials in office technology subjects.